Pembuatan Objek 3D Candi Badut Menggunakan Metode Photogrammetry - Benjamin Septa Pardamean; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Based on its function, the media as a source of information plays a very important role in learning, by delivering accurate information, the information conveyed can be received clearly. One of the digital media is three-dimensional media that provides visual information on objects such as colors, textures, shapes, and others. One of the methods in making 3D objects is by using the photogrammetry method. The photogrammetry method is the process of making 3D objects using many photos captured by the camera that will be integrated into a software and processed into 3D objects. In this research, the photogrammetric method in making 3D objects of Candi Badut, using UAV in taking photos, is then processed in the Meshroom software which consists of StructureFromMotion, DepthMap, Meshing, and Texturing stages, which produce 3D objects and then reprocessed in the Blender 3D. The resulting 3D object results can be used as digital assets such as the introduction of tourist objects, video games, animation and others. The 3D object of Candi Badut was tested to measure the level of accuracy using the Root Mean Square Error (RMSE) method by comparing the measurement results in the software with the measurement results in the field. The test results obtained are RMSE of 0.0734meter where the 3D object of Candi Badut produced by the photogrammetry method has approached the object of Candi Badut in the real world.